Hypothyroidism And Stress- A Review Article - Sujata; Gupta, Divya; Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2020)
Due to modernization and increased stress in daily life, life style have been changed which results into many endocrinal diseases, Hypothyroidism is one among them. Stress plays a major role in hypothyroidism pathogenesis. In Samhitas there is no direct reference of hypothyroidism but due to increased stress in our routine life it alters hypothalamus-pituitary-thyroid axis activity. In contemporary system of medicine, the drug of choice for Hypothyroidism is levothyroxine. Side effects of these drugs are increased hunger, muscle weakness, irregular periods, diarrhoea, excessive sweating, fever, hair loss, etc. In Ayurveda there is not any direct reference of chikitsa of hypothyroidism but it can be managed by using stress relieving and kapha vatahar chikitsa like shirodhara, abhyanga, various medhya rasyana. Laughter therapy and yoga also plays a major role in reducing stress. This study was carried out using through various ayurvedic classical text, pubmed, google scholar as well as available modern literature, collected data and observation were presented in a scientific manner. The review will be beneficial to understand the pathogenesis of hypothyroidism and modify the line of treatment of disease.